2017
DOI: 10.1007/s11222-017-9771-5
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel and Multi-index Monte Carlo methods for the McKean–Vlasov equation

Abstract: We address the approximation of functionals depending on a system of particles, described by stochastic differential equations (SDEs), in the mean-field limit when the number of particles approaches infinity. This problem is equivalent to estimating the weak solution of the limiting McKean-Vlasov SDE. To that end, our approach uses systems with finite numbers of particles and a timestepping scheme. In this case, there are two discretization parameters: the number of time steps and the number of particles. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…We also have the following estimates on the quantities arising inμ X (α,β) t , which will be used repeatedly throughout the paper. The first estimate (12) for Φ can be obtained immediately from Grönwall's lemma and the definition of Φ in (11).The other results can be deduced similarly and the details are postponed until Appendix A.…”
Section: Preliminaries On Linear Sdes With Jumpsmentioning
confidence: 98%
See 1 more Smart Citation
“…We also have the following estimates on the quantities arising inμ X (α,β) t , which will be used repeatedly throughout the paper. The first estimate (12) for Φ can be obtained immediately from Grönwall's lemma and the definition of Φ in (11).The other results can be deduced similarly and the details are postponed until Appendix A.…”
Section: Preliminaries On Linear Sdes With Jumpsmentioning
confidence: 98%
“…It is usually shown that, in the limit N → ∞, the empirical law of a Markovian system with N interacting particles, converges to the law of the solution to the MK-V SDE under study, which can be then approximated via timediscretization and simulation. Following the work by Sznitman in [21], where the first propagation of chaos result was proved, many authors have contributed to this stream of literature, see, for example, [2], [23], [11], and [20], by supposing different forms and regularity assumptions on the MK-V SDE coefficients. Although a very powerful approximating tool which is applicable in many settings, the simulation of large-particle systems can be computationally very expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The particle systems j and j ′ , j = j ′ , driven by (w i,j ) i,j and (w i,j ′ ) i,j respectively, are independent. This idea for finite time simulations has been proposed in [HAT16]. Another approach that we investigate are self-interacting diffusion…”
Section: Introductionmentioning
confidence: 99%
“…Second, imposing slightly stricter regularity assumptions, we can prove better asymptotic efficiency results for this method than for the original one. And third, creating a rigorous convergence theory for the new MLEnKF method is a stepping stone towards a multi-index Ensemble Kalman filtering (MIEnKF) method; See [19] for highly efficient approximations of McKean-Vlasov dynamics by the multi-index Monte Carlo method, and Appendix D for a sketch of the said extension to MIEnKF.…”
mentioning
confidence: 99%
“…Following the construction of multi-index Monte Carlo mehods for mean-field dynamics approximations [19], we sketch an extension from MLEnKF to MIEnKF. On the particle level, this extension may be viewed as an extension from two-particle coupling to four-particle coupling.…”
mentioning
confidence: 99%